Educational peer group teenager to teenager’s knowledge about bullying - Maria Ulfah Kurnia Dewi (Jurnal Kebidanan, 2021)
The phenomenon of bullying is not only seen from the point of view of the individual perpetrators and victims, but it focuses more on the social aspects behind the phenomenon. The formation and development of youth classes are a means to provide knowledge for adolescents about health. The youth class program must be carried out continuously in schools. The National Survey of Child and Adolescent Life Experiences (SNPHAR) by the Ministry of Women's Empowerment and Child Protection (KPPPA), 2018 revealed that 3 out of 4 adolescent children who had experienced one or more types of violence reported that the perpetrators of violence were friends or their peers. The purpose of this study was to determine the relationship between adolescent peer group education and adolescent knowledge about bullying. quantitative research with analytic survey design with the population is teenagers at the Ning Amriyah Soepardo Kendal Orphanage. The sample used is 30 respondents using total sampling. The research instrument used attendance data and questionnaires. The variables studied were adolescent peer group education and adolescent knowledge about bullying. The results showed that there was a relationship between adolescent peer group education and the level of adolescent knowledge about bullying (pvalue < α).